Efektifitas Senam Yoga dan Kompres Hangat terhadap Penurunan Nyeri Dismenorea pada Remaja Putri di SMP Negeri 19 Kota Ambon - Vicha Vioricha Pamellla Tomasoa; Ageng Septa Rini; Agustina . (Elisabeth Health Jurnal, 2023)
Adolescence is a period of human transition from childhood toadulthood, marked by an acceleration of physical, emotional,mental and social development. The physical changes experienced by adolescents have a major influence on the development of the adolescent”s soul ,namely the growth of the body,such as the body gelting taller and longer. Followed by the start of the functioning of the reproductive organs (marked by menstruation in women) this menstruation is a secondary sexual sign in adolescents and there are some adolescents who experience disturbances during menstruation , namely experiencing pain during menstruation or dysmenorrhea. The purpose of this study was to determine the effectiveness of yoga execise and warm compresses in reducing dysmenorrhea pain in young woman at SMP Negeri 19 Ambon City in 2022 . This type of quantitative research used the Quasy Expeiment with a pretest-posttest approach the sampling technique was a total sampling of 60 samples with Wilcoxon analysis test . Results there is a effect of yoga on reducing dysmenorrhea pain value 0,04 and warm compresses on reducing dysmenorrhea pain in young woman at SMP Negeri 19 Ambon City in 2022 p value 0.003 . Conclusion Yoga exercises and warm compresses are effective in reducing the pain of dysmenorrhea, but the reduction in pain that can be felt immediately when the intervention is given is warm compresses. Management warm compresses are more effectively used to treat dysmenorrhea. From this research it is suggested to be able to provide an alternative solution for schools in dealing with dysmenorrhea during the menstrual cycle in female students at school, so that they can carry out their daily activities as usual, especially participating in learning at school